2022
DOI: 10.1111/hex.13593
|View full text |Cite
|
Sign up to set email alerts
|

Widening or narrowing inequalities? The equity implications of digital tools to support COVID‐19 contact tracing: A qualitative study

Abstract: Background: As digital tools are increasingly used to support COVID-19 contact tracing, the equity implications must be considered. As part of a study to understand the public's views of digital contact tracing tools developed for the national 'Test and Protect' programme in Scotland, we aimed to explore the views of groups often excluded from such discussions. This paper reports on their views about the potential for contact tracing to exacerbate inequalities.Methods: A qualitative study was carried out; inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…As a result, they have limited learning resources and depend on limited printed books. A similar result found by O' Donnell et al [14], asserted that the powerlessness to afford smartphones and the data for the internet, the lack of pro ciency in digital tools and standard language for academic activities are the main barrier to students living in poverty for better class engagement including the additional cost and efforts. It is sensitive ceased to use multiple resources for learning.…”
Section: Discussionsupporting
confidence: 62%
“…As a result, they have limited learning resources and depend on limited printed books. A similar result found by O' Donnell et al [14], asserted that the powerlessness to afford smartphones and the data for the internet, the lack of pro ciency in digital tools and standard language for academic activities are the main barrier to students living in poverty for better class engagement including the additional cost and efforts. It is sensitive ceased to use multiple resources for learning.…”
Section: Discussionsupporting
confidence: 62%
“…Previous research examining perspectives of the NZCTA, 8 and of DCT apps in other settings 2 have similarly identified a lack of trust as a significant barrier to adoption. For instance, O'Donnell et al 3 emphasised the importance of trust in the overall system, not just DCT apps, stating that many individuals expressed concerns about their data potentially being shared for benefits checks or for those in search of asylum. Our research highlights how distrust is deeply embedded in social contexts, entrenched in a colonial history that has systematically marginalised community members.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Research examining public perspectives of DCT has identified barriers to adoption, including low access to ICTs, apprehensions regarding cybersecurity and privacy and a lack of trust in the government, 2 raising concerns that DCT could have a lower uptake amongst some groups who are at greater risk of more severe illness from COVID‐19. 1 However, the perspectives and experiences of these higher‐risk groups of DCT have been underrepresented in qualitative research (for a notable exception, see O'Donnell et al 3 ). This is problematic, as it underrepresents these communities' information needs, the systemic and structural barriers to adoption and how current systems could be reconfigured to better serve communities.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show similar determinants of the intention to accept and adopt digital tools for CT, such as privacy and security concerns [ 31 , 40 ], feelings of shame and stigma [ 41 ], trust in technologies for CT [ 42 44 ], social responsibility [ 29 , 31 ], performance expectancy, perceived benefits [ 29 ], and understanding [ 40 , 44 ]. More specifically, it was found that users need to have trust in their data being stored safely and that such tools are only used for the control of COVID-19 [ 43 ]. Besides this, they need to have experience in -, access to -, and competence in using digital tools (i.e., “digital literacy”), to understand and believe in the potential benefits of such tools, and to be motivated to contribute to the greater good (i.e., the public health) [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%